2018
DOI: 10.4103/iju.iju_184_17
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic lower urinary tract dysfunction in sacral agenesis: Potentially high risk?

Abstract: Introduction:Sacral agenesis (SA) is a caudal regression anomaly that can cause neurogenic bladder but is not generally recognized as high risk. We studied the clinical presentation, upper urinary tract, bone and spine abnormalities, and urodynamic findings in patients with SA and compared them with related high-risk conditions, anorectal malformation (ARM), and cloacal malformation.Materials and Methods:Patient records between May 2011 and December 2015 were identified and grouped into isolated SA without an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Connective tissue contains collagen fibrils, embedded in a ground substance, that have a greater intrinsic elastic modulus than muscle tissue [ 23 , 24 ]. This is consistent with poor compliance and upper tract damage in a large proportion of patients with myelomeningocele or sacral agenesis [ 25 , 26 ], as well as increased connective tissue deposition in animal models and humans with spinal cord injury, in particular deposition of the subtype of collagen (type-I) with greater intrinsic stiffness [ 27 , 28 ]. Medical management of neurogenic bladders with antimuscarinic agents or botulinum toxin can improve continence and renal outcomes by reducing detrusor overactivity and improving compliance.…”
Section: Discussionsupporting
confidence: 55%
“…Connective tissue contains collagen fibrils, embedded in a ground substance, that have a greater intrinsic elastic modulus than muscle tissue [ 23 , 24 ]. This is consistent with poor compliance and upper tract damage in a large proportion of patients with myelomeningocele or sacral agenesis [ 25 , 26 ], as well as increased connective tissue deposition in animal models and humans with spinal cord injury, in particular deposition of the subtype of collagen (type-I) with greater intrinsic stiffness [ 27 , 28 ]. Medical management of neurogenic bladders with antimuscarinic agents or botulinum toxin can improve continence and renal outcomes by reducing detrusor overactivity and improving compliance.…”
Section: Discussionsupporting
confidence: 55%
“…Sinha et al . [ 1 ] in their study reported that children with sacral agenesis may also have neurogenic bladders that could lead to renal damage, similar to that seen in children with anorectal malformations.…”
Section: Sacral Agenesis and Lower Urinary Tract Dysfunctionmentioning
confidence: 82%
“…An unfavorable factor is vesicoureteral reflux, which, together with frequent urinary tract infections, may affect kidney function in the future. Sinha, in his interesting research, observed a long-standing lower urinary symptoms in all patients with sacral agenesis, as well as high prevalence of upper tract changes [ 50 ]. Isolated sacral agenesis may be a cause of neurogenic bladder that often presents itself late and may result in renal damage [ 50 ].…”
Section: Urogenital and Gastrointestinal Problemsmentioning
confidence: 99%
“…Sinha, in his interesting research, observed a long-standing lower urinary symptoms in all patients with sacral agenesis, as well as high prevalence of upper tract changes [ 50 ]. Isolated sacral agenesis may be a cause of neurogenic bladder that often presents itself late and may result in renal damage [ 50 ]. Esposito recommended a special diagnostic protocol for all newborns at increased risk of urologic anomalies.…”
Section: Urogenital and Gastrointestinal Problemsmentioning
confidence: 99%